Compatibility of the cowpea seed treatment with fungicides and inoculation with Bradyrhizobium strains - Silva Neto, Manoel Luis da; Smiderle, Oscar José; Silva, Krisle da; Fernandes Júnior, Paulo Ivan; Xavier, Gustavo Ribeiro; Zilli, Jerri Édson (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the compatibility of seed treatment with fungicides and Bradyrhizobium strains inoculation for cowpea. Cell survival on seeds of cultivar BRS Guariba treated or not with fungicides (fludioxonil, carbendazim, carbendazim + thiram, and carboxin + thiram) and inoculated or not with Bradyrhizobium (strains UFLA3‑84, BR 3267, INPA3‑11B, and BR 3262) were evaluated in laboratory. Another experiment was carried out in greenhouse, in Leonard jars, using the same treatments. The following were evaluated: shoot dry matter weight, besides number and dry matter weight of nodules 25 days after plant emergence. Two experiments were performed in the field with the strain BR 3262, with fungicides on the seeds: one in a first cultivation area and the other in an area previously cultivated with annual crops. Nodule number, nodule dry weight, and shoot dry matter weight were evaluated at 35 days, and grain yield at harvest. Fungicides did not have significant effect on Bradyrhizobium survival, plant nodulation, and grain yield, which was, in average, higher than 1,200 kg ha‑1. Cowpea seed treatment with fungicides is compatible with the inoculation of the evaluated strains.